First record of Mimogonus fumator (Fauvel, 1889) (Coleoptera: Staphylinidae: Osoriinae) in the USA, with a synopsis of the Osoriinae of the Southeastern USA - Pandolfi, Alessandra; Kelly, Sandor; Irmler, Ulrich; Bohlen, Patrick (Zootaxa, 2024)
The discovery of Mimogonus fumator (Fauvel, 1889) in a suburban area in Central Florida marks the first record of this pantropical species in the United States of America. This finding emphasizes the critical significance of insect monitoring in urban environments, as it unveils the potential for detecting non-native and potentially invasive species accidentally transported through soil and ornamental plants. A taxonomic key and distributional checklist for the known species of the subfamily Osoriinae in the Southeastern United States are also provided. These resources aim to enhance our understanding of the regional insect fauna and provide useful tools for future detection.